A Statistical Analysis of the Nitrogenous Composition and its Relationship with the Microbiological Safety of the Hassan Spring Water in Al-Qadmous City - خميس عطية; ياسين مفيد; رقية مها (Latakia University Journal -Medical Sciences Series, 2021)
Water is the basis of life on our planet, Ground-water is an important source of drinking water in many countries, but as a result of agricultural, industrial and demographic development, it has been exposed to many pollutants that have threatened its suitability for drinking and irrigation. Microbial contamination (Total and Faecal coliforms) and nitrogenous water-pollutants (Nitrite and Nitrate) were measured monthly from July 2019 to June 2020, at the Hassan spring in Al-Qadmous region. Both Nitrite and Nitrate concentrations varied significantly through July-October (at higher than 0.012 and 6 mg/L respectively), while they remained below these levels through December-June. The total coliforms showed slight increase during the year, at around 160±11 CFU/100mL, while the faecal coliforms were not detectable through July-October but appeared in November and showed slight increase through December-June, at around the level 73±12 CFU/100Ml. Rigorous Analysis of Variance (Excel-ANOVA) and Cluster Analysis (SPSS) confirmed the visibly significant change (p<<0.05), in a specified time (November,2019), in the pollutant levels or in their direction of change. Based on the appearance of faecal bacteria and the sudden change in the combined pattern of the calculated statistical and dynamic parameters, we hypothesized that nitrogenous ions in water could be used as indicators for microbial contamination but careful literature review did not substantiate this expectation. Nonetheless, the coincidence that the two changes happened at the same time keeps the possibility that a common reason triggered both changes. Both total and faecal coliforms counts were above the Syrian and International standards which raises the need to decontaminate the water of Hassan spring.